Injury incidence among adolescent and senior basketball players: a prospective study in 19 teams across an entire season - Stojanovic, E.; Faude, O.; Scanlan, A. T.; Jakovljevic, V.; Cosic, M.; Kocic, M.; Radovanovic, D. (The Physician and Sportsmedicine, 2024)
Objective To quantify and compare injury incidence between national-level, adolescent and regional-level, senior, male basketball players competing in Serbia overall and according to injury mechanism (contact, non-contact, or overuse), exposure setting (training or games), and history (new or recurrent).